Antifungal Activity, Synergism with Fluconazole or Amphotericin B and Potential Mechanism of Direct Current against Candida albicans Biofilms and Persisters - Peihui Zou; Jia Liu; Peng Li; Qingxian Luan (MDPI AG, 2024)
Candida albicans, as a notorious fungal pathogen, is associated with high morbidity and mortality worldwide due to its ability to form biofilms and persisters that can withstand currently available antifungals. Direct current (DC) has demonstrated a promising antimicrobial effect and synergistic effect with antimicrobials against various infections. Here, we first found DC exerted a killing effect on C. albicans planktonic and biofilm cells. Moreover, DC showed a synergistic effect with fluconazole (FLC) and amphotericin B (AMB). Notably, near-to-complete eradication of AMB-tolerant C. albicans biofilm persisters was achieved upon DC treatment. Next, the mechanism of action of DC was explored through mapping the genes and proteomic profiles of DC-treated C. albicans. The multi-omics analysis, quantitative real-time PCR and assay of reactive oxygen species (ROS) demonstrated DC exerted an antifungal effect on C. albicans by increasing cellular oxidative stress. As revealed by multiple analyses (e.g., protein assay based on absorbance at 280 nm and rhodamine 6G assay), DC was able to enhance membrane permeability, inhibit drug efflux and increase cellular FLC/AMB concentration of C. albicans, thereby mediating its synergism with the antifungals. Furthermore, DC inhibited superoxide dismutase 2 (SOD2) expression and manganese-containing SOD (Mn SOD) activity, leading to ROS production and enhanced killing of C. albicans biofilm persisters. The current findings demonstrate that the adjunctive use of DC in combination with antifungals is a promising strategy for effective control of C. albicans infections and management of antifungal resistance/tolerance in Candida biofilms.